2020
DOI: 10.1101/2020.11.12.20230870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing COVID-19 control with asymptomatic surveillance testing in a university environment

Abstract: The high proportion of transmission events derived from asymptomatic or presymptomatic infections make SARS-CoV-2, the causative agent in COVID-19, difficult to control through the traditional non-pharmaceutical interventions (NPIs) of symptom-based isolation and contact tracing. As a consequence, many US universities are developing asymptomatic surveillance testing labs, to augment existing NPIs and control outbreaks on campus. We built a stochastic branching process model of COVID-19 dynamics at UC Berkeley … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Our findings support the conclusions of Paltiel, et al [32], who found that frequent (every 2 days), low-sensitivity testing might be necessary in order to allow for college reopening. Moreover, several modeling studies have found that diagnostic testing of symptomatic patients alone is insufficient for outbreak control, and must be supplemented by randomized surveillance testing of the asymptomatic population [8, 11, 22, 32]. Indeed, under randomized and uniformly distributed surveillance testing of the entire non-isolated population, we find that frequent testing of the entire population can flatten the daily incidence curve and significantly decrease the cumulative size of the outbreak.…”
Section: Discussionmentioning
confidence: 84%
“…Our findings support the conclusions of Paltiel, et al [32], who found that frequent (every 2 days), low-sensitivity testing might be necessary in order to allow for college reopening. Moreover, several modeling studies have found that diagnostic testing of symptomatic patients alone is insufficient for outbreak control, and must be supplemented by randomized surveillance testing of the asymptomatic population [8, 11, 22, 32]. Indeed, under randomized and uniformly distributed surveillance testing of the entire non-isolated population, we find that frequent testing of the entire population can flatten the daily incidence curve and significantly decrease the cumulative size of the outbreak.…”
Section: Discussionmentioning
confidence: 84%
“…Our findings support the conclusions of Paltiel, et al [ 6 ], who found that frequent (every 2 days), low-sensitivity testing might be necessary in order to allow for college reopening. Moreover, several modeling studies have found that diagnostic testing of symptomatic patients alone is insufficient for outbreak control, and must be supplemented by randomized surveillance testing of the asymptomatic population [ 6 , 25 , 42 , 43 ]. Indeed, under randomized and uniformly distributed surveillance testing of the entire non-isolated population, we find that frequent testing of the entire population can flatten the daily incidence curve and significantly decrease the cumulative size of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…As we have stated, we have relatively modest ambitions in this study of exploring how the size of mixing groups (considered as classes here) impact the time course of epidemics in partitioned populations. Other studies have provided highly detailed analyses of models with many realistic assumptions, contact networks and NPIs included (Ferguson et al, 2020; Kucharski et al, 2020; Firth et al, 2020; Kain et al, 2021) including in university settings (Bahl et al, 2020; Brook et al, 2020; Cashore et al, 2020; Lopman et al, 2020). If our study were to be applied to more realistic scenarios or to form the basis of decision making, some key further additions would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As countries move to reopen these settings, an important question is how classes can be organised to minimise further disruption to students’ education whilst limiting epidemic spread. There have been some excellent, in-depth modelling studies of infection spread in educational settings, especially universities, with a range of NPIs included, often with a focus on testing and isolation strategies (Bahl et al, 2020; Brook et al, 2020; Cashore et al, 2020; Lopman et al, 2020). Here we focus on the question of how class sizes may impact an epidemic.…”
Section: Introductionmentioning
confidence: 99%